Responsible Parenthood: Reproduction and Religion in Post-War Britain - Merricks, Patrick T. (The journal of religious history, literature and culture, 2018)
'Man's development is influenced, not only by inborn qualities and dispositions and by environment, but also by a spiritual factor lying beyond both - namely, the grace of God.' Thus wrote Reverend Derrick Sherwin Bailey (1910-84) in The Eugenics Review in 1959. In the 1950s and 1960s, British churchmen and eugenicists shared two major interests: the growing population, and emerging fertility treatments. In engaging with these issues, this article explores a subject of increasing interest and importance to present and future society. The introduction outlines issues of agreement and contention between eugenicists and churchmen on 'responsible parenthood'; the first section details debates on contraception surrounding the 1958 Lambeth Conference and the passing of new government legislation on birth control and abortion a decade later; the second section explores contrasting opinions on artificial insemination and its use to improve society; and the conclusion draws parallels between these opinions and how parenthood is discussed today. If eugenic and religious opinions were influential in shaping the understanding of reproductive technologies and habits in mid-century Britain, implementing new scientific techniques to improve the human species should heighten our inherent sense of moral responsibility.